“Determinación de la Huella de Carbono en la Universidad Técnica Estatal de Quevedo, provincia de Los Ríos” - García García, Selena Lissette (2020)
The purpose of this research was to determine the Carbon Footprint at the State Technical University of Quevedo, the results of which made it possible to propose effective plans to minimize GHG emissions. The methodology of the ISO UNE 14064-1: 2018 standard was applied, in its most recent update it establishes the calculation through six categories, of which four were considered, for its development on-site inspections were carried out, data were extracted from the Purchasing Portal Public, Ministry of Environment and Water Ecuador and the personnel were questioned. Once the results have been obtained, it is concluded that the total emissions of carbon dioxide equivalent to the year 2019 was 2,546.89 t 〖CO〗_2eq, which indicates that 1.35 t 〖〖CO〗_2eq are emitted for each person. When analyzing the data for each category used, it indicates that Category 1 is the one that contributes the most emissions with a value of 3,878.06 t 〖CO〗_2eq, it is mainly the product of fluorinated air conditioning gases and mobile combustion from transport; Category 2 belongs to electricity consumption reaching 862.17 t 〖CO〗_2eq, in the case of Category 4 it emitted 1116.18 t 〖CO〗_2eqinto the atmosphere, it should be noted that it is due to the fact that office furniture was counted that have been obtained through the years, in total are 702.0775 t 〖CO〗_2eq, and Category 6 considers the constructions of the year 2019 reaching 6690.47 t 〖CO〗_2eq. Therefore, it is concluded that it is pertinent that the UTEQ correctly apply the plans described in this project. Keywords: Carbon footprint, Carbon dioxide equivalent, emission factor, greenhouse gases.